2017
DOI: 10.1038/s41538-017-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Four years post-horsegate: an update of measures and actions put in place following the horsemeat incident of 2013

Abstract: Complexities in food supply chains were highlighted by the so called ‘horsegate’ crisis in 2013, where beef meat was fraudulently adulterated with horse meat causing widespread recalls and subsequent investigations across both retail and food service markets in the European Union (EU). The beef supply chain is a complex supply chain, with global (EU and Non EU) sourcing strategies in order to secure supply. However, managing these complex supply chains can be difficult and consequentially can expose vulnerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…the 2013 EU horse meat scandal, where beef was replaced with horse meat demonstrated that, in the EU, oversight of the meat industry and its traceability system was not as robust as consumers were led to believe. 5…”
Section: Introductionmentioning
confidence: 99%
“…the 2013 EU horse meat scandal, where beef was replaced with horse meat demonstrated that, in the EU, oversight of the meat industry and its traceability system was not as robust as consumers were led to believe. 5…”
Section: Introductionmentioning
confidence: 99%
“…The fact that food companies employ staff who have a primary responsibility for the ethical conduct of their organisations does not however absolve other staff of the responsibility for acting ethically in the pursuance of company objectives. Consider the example of the so‐called Horsegate [6] incident of 2013 to appreciate the extent to which food business staff straying from the path of moral rectitude in pursuit of profit can bring the values of an industry sector sharply into ethical question and disrepute.…”
Section: The Territory Of Food Ethicsmentioning
confidence: 99%
“…Ellis, Muhamadali, Haughey, Elliott, and Goodacre [6] stressed that the ever-expanding portfolio of analytical methods, techniques and technologies in food control and future pervasive and predictive computation will together take on the role of a technology-based capable guardian for food systems. Simultaneously, more than ever before, experts recognize that food integrity is a challenge that requires a joint strategy and coordinated efforts involving all stakeholders, and that a strengthening of the collaboration between industry and governments is necessary [7]. The development of an integrated private–public strategy requires clearly defined roles for each participating stakeholder and clarity and shared agreement on the specific purpose [8].…”
Section: Introductionmentioning
confidence: 99%
“…Following the horsemeat incident, several actions were taken, and new initiatives were set up. For example, in the United Kingdom, the incident led to the establishment of the Food Industry Intelligence Network (FIIN), and on a European level it led to the Food Fraud Network (FFN), both aiming at the type of intelligence gathering that the Elliott review recommended [7].…”
Section: Introductionmentioning
confidence: 99%